Aspectos sanitários e adaptabilidade de caprinos da raça canindé em região semiárida - Fonseca, Elanne de Paiva (2019)
The creation of locally adapted ruminants, such as Canindé goats, is a characteristic of some production systems in the northeastern region of Brazil. In this context, gastrointestinal parasites and caseous lymphadenitis are responsible for the decrease in the population of these animals, representing one of the main problems observed in goat breeding. The objective of the present study was to evaluate the adaptive conditions of Canindé goats in relation to the physiological, clinical, hematological and biochemical aspects during the year and its resistance to gastrointestinal endoparasites and caseous lymp hadenitis, created in the semiarid region. A total of 180 Canindé goats were used in the semi-arid region. Among the variables evaluated are: environmental, physiological aspects, hematological profile and serum biochemical values, weight, body condition score and health status. The variables were evaluated in two periods of the year: rainy and dry. The dissertation is composed of three chapters: (I) Theoretical reference, covering subjects related to the characterization of semiarid productive systems and the importance of genetic resources of locally adapted breeds (II) An evaluation of thermoregulation and performance of Canindé goats during the dry and rainy season; (III) A check of the presence of gastrointestinal endoparasites and the relation of hematological and biochemical values and the diagnosis of caseous lymphadenitis. The study reports that there was a difference between the periods, but, in general context, did not escape from that recommended for the species, taking into account the environmental conditions of the semiarid. These divergent results from the one recommended for the species may be due to the particular characteristics of the breed and its adaptability. All these aspects studied serve as a basis for understanding the physiology and proper management of locally adapted goats, in order to maintain their genetic resources